Impact of Transport Cost and Travel Time on Trade under China-Pakistan Economic Corridor (CPEC) - Khalid Mehmood Alam; Xuemei Li; Saranjam Baig (Journal of Advanced Transportation)
China is the second biggest economy in the world and almost 40% of its trade in 2016 is transported through the South China Sea. China needs a small, secure, and low-cost path to trade with Europe and the Middle East and China-Pakistan Economic Corridor (CPEC) is a feasible solution to this requirement. This research analyzes the effect of CPEC on trade in terms of transport cost and travel time. In addition, the study compares the existing routes and the new CPEC route. The research methodology consists of qualitative and descriptive statistical methods. The variables (transport cost and travel time) are calculated and compared for both the existing route and new CPEC route. The results show that transport cost for 40-foot container between Kashgar and destination ports in the Middle East is decreased by about $1450 dollars and for destination ports in Europe is decreased by $1350 dollars. Additionally, travel time is decreased by 21 to 24 days for destination ports in the Middle East and 21 days for destination ports in Europe. The distance from Kashgar to destination ports in the Middle East and Europe is decreased by 11,000 to 13,000 km.